Pengaruh Penambahan Zeolit dan Karbon Aktif pada Papan Partikel Berbahan Dasar Ampas Tebu (Saccharum officinarum L.) dan Biomassa Lignoselulosa terhadap Kekuatan Mekanik serta Potensi Adsorptif terhadap Gas Polutan - Bernice Kinan Pindyastama; Almahabah Nur Illahi; Fatichah Lutfi Zata Aqmar; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2026)
Indonesia is one of the largest sugarcane producers in Southeast Asia, but the bagasse waste produced is often underutilized and can pollute the environment. This study developed particle boards based on sugarcane bagasse and lignocellulosic biomass with the addition of zeolite and activated carbon. This study focused on observing the effect of adding zeolite and activated carbon as reinforcing materials for particle boards as well as adsorbents for pollutant gases. The method used in this study was quantitative research with an experimental approach. Data collection was conducted through observation and literature review. The boards were made by mixing biomass, bagasse, zeolite, activated carbon, resin, and catalyst in certain proportions, then molded and pressed until dry. Testing was carried out through load resistance testing (ASTM D1037-12), water absorption testing (SNI 03-2105-2006), and pollutant gas adsorption testing (SNI 19-7117.7-2005). The results showed that the board could withstand loads of up to 62 kg, had a water absorption capacity of 36.4%, and a CO gas adsorption efficiency of 44%. These findings prove that the addition of zeolite and activated carbon effectively increases mechanical strength and adsorption function, making particle boards an environmentally friendly construction solution and a means of reducing air pollutants.